2016
DOI: 10.1039/c6py00920d
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous enhancement of performance and insensitivity to active layer thickness for OPVs by functionalizing π-spacer's side chain

Abstract: A novel BTI based copolymer was designed by incorporating a decylthio modified π-spacer into the backbone for improving the photovoltaic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The n ‐decyl chain in the previously reported polymer 59 a was replaced with an alkylthio chain to enhance the backbone planarity and π–π stacking, and the resulting polymer donor 59 b yielded an improved PCE of 7.14 % when blended with PC 71 BM ([6,6]‐phenyl C 71 butyric acid methyl ester) than 59 a based OSCs with a moderate PCE of 6.51 % under their optimized device fabrication condition. Notably, a low sensitivity of the photovoltaic performance of 59 b :PC 71 BM solar cells for the active layer thickness was observed such that a PCE above 7.0 % can still be maintained with a 270 nm thickness . The wide band gap polymer 60 with an alkyl or π‐spacer alkylthio chain on the BDT unit was designed and synthesized by Yang et al.…”
Section: Bti‐based Polymer Semiconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The n ‐decyl chain in the previously reported polymer 59 a was replaced with an alkylthio chain to enhance the backbone planarity and π–π stacking, and the resulting polymer donor 59 b yielded an improved PCE of 7.14 % when blended with PC 71 BM ([6,6]‐phenyl C 71 butyric acid methyl ester) than 59 a based OSCs with a moderate PCE of 6.51 % under their optimized device fabrication condition. Notably, a low sensitivity of the photovoltaic performance of 59 b :PC 71 BM solar cells for the active layer thickness was observed such that a PCE above 7.0 % can still be maintained with a 270 nm thickness . The wide band gap polymer 60 with an alkyl or π‐spacer alkylthio chain on the BDT unit was designed and synthesized by Yang et al.…”
Section: Bti‐based Polymer Semiconductorsmentioning
confidence: 99%
“…Notably,alow sensitivity of the photovoltaic performance of 59 b:PC 71 BM solar cells for the active layer thickness was observeds uch that aP CE above 7.0 %c an still be maintained with a2 70 nm thickness. [76] The wide band gap polymer 60 with an alkyl or p-spacer alkylthio chain on the BDT unit was designed and synthesized by Yang et al Fullerene-based OSCs using 60 b as the donor polymer exhibited ap romising PCE of 9.42 %w ith a V oc of 0.91 V, J sc of 14.53 mA cm À2 ,a nd FF of 71.29 %. The PCE is much highert han that of OSCs containing 60 a with an alkyl sidechain, whichisl ikely due to the reduced steric hindrance when using alkylthio-functionalized thiophene as the spacer.…”
Section: Bti-based Polymer Semiconductorsmentioning
confidence: 99%
“…Compared with its analogue PBTI3T, the hole mobility of the PBTI3T-S/PC 71 BM blend is 1.29 × 10 –2 cm –2 V –1 s –1 , much higher than that of the PBTI3T/PC 71 BM blend (1.15 × 10 –3 cm –2 V –1 s –1 ). The PCE values are all above 7% for the copolymer PBTI3T-S as active layer thickness varies from 115 to 271 nm . Recently, Bo et al reported two alkylthio-substituted benzothiadiazole-quaterthiophene-based conjugated polymers.…”
Section: Introductionmentioning
confidence: 98%
“…The PCE values are all above 7% for the copolymer PBTI3T-S as active layer thickness varies from 115 to 271 nm. 28 Recently, Bo et al reported two alkylthio-substituted benzothiadiazole-quaterthiophene-based conjugated polymers. PSCs based on fluorinated polymer P1:PC 71 BM gave a PCE of 7.76%.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, the incorporation of planar units such as anthracene, perylene, and pyrene has been demonstrated to enhance the π–π interaction of polymers, but the dissimilar chemical structure of the third unit could cause an adverse effect on molecular packing and film morphology. To eliminate this negative effect, the incorporation of a structurally similar third component into the polymer backbone has rarely been investigated. …”
Section: Introductionmentioning
confidence: 99%